EVALUATION OF EX VIVO THROMBOLYTIC ACTIVITY AND IN VITRO ANTI-INFLAMMATORY ACTIVITY OF THESPESIA POPULNEA LEAF EXTRACT (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
Thrombotic disorders like myocardial and cerebral infarction are fatal blood clotting related diseases. Synthetic therapeutics used in such disorders has serious adverse effects, so there is a need to investigate some more safe natural thrombolytic agents. Present study is a preliminary work towards such endeavors. During this study analysis of thrombolytic activity and anti-inflammatory activity of Thespesia populnea leaf extract using a simple and quick in vitro clot lysis assay was performed. Various concentrations of leaf extract i.e. 200µg/ml; 400µg/ml and 600µg/ml were tested at various time intervals including; 24, 48 and 72 hours duration of incubation at 37°C for observing maximum clot lysis. The result findings indicated that concentrations of leaf extract enhanced the percentage of clot lysis in dose dependent manner along with the incubation time factor. However; streptokinase SK a reference standard and water were used as a positive and negative control showed clot lysis maximum 96.35% and 35.22% in 72 hours of incubation respectively. Alcohol extract of whole plant of Thespesia populnea (Family: Malvaceae) was assessed for its anti-inflammatory activity by in vitro methods. In vitro anti-inflammatory activity was evaluated using albumin denaturation assay at different concentrations. Diclofenac sodium was used as standard drug. The results showed that Thespesia populnea alcohol extract at a concentration range of 400-1600µl significantly protects from protein denaturation.